Kajian dan Evaluasi Bencana Tanah Longsor di Kecamatan Tanjungsari terhadap RTRW Kabupaten Bogor - Sri Fauza Pratiwi; Masita Dwi Mandini Manessa; S Supriatna (Department of Urban and Regional Planning, Diponegoro University, 2022)
Landslide is one of the natural disasters that often occurs in Indonesia, which has various geographical conditions and different topography of different areas. Landslide is one of the natural disasters that often occurs in Indonesia as a country that has various geographical conditions and different topography of different areas. However, an exhaustive study of spatial use which includes suitability assessment between the Regional Spatial Plan (Rencana Tata Ruang Wilayah/RTRW) documents and regional potential and other factors such as disasters is still rarely carried out. Tanjungsari District, Bogor Regency is an area that has experienced landslides in January 2020. The purpose of this study was to evaluate the RTRW of Bogor Regency against landslides in Tanjungsari District. The vulnerability of a site to landslides is caused by several factors which are used as parameters in this study. The parameters are land use, rainfall, slope, geology, and soil type. Each parameter used is given a score and weight then an overlay of each parameter weighting is carried out to obtain a landslide susceptibility map. Furthermore, a descriptive spatial analysis of the landslide hazard was carried out on the spatial plan of the Bogor Regency. The results when compared with the existing conditions, the use of plantation land and forest areas overlap with areas prone to landslides. Thus, it is necessary to review the existing RTRW maps to reduce the impact of landslides.